Microclimate and thermal comfort indices in silvopastoral systems under different planting directions and seasons - Rafael P. de Carvalho; Debora M. Heid; Livia M. C. Davide; Ligia M. M. da S. Piletti; Fernanda L. F. de Jesus; Antonio L. Viegas Neto (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The orientation of tree-rows in a silvopastoral system associated with different seasons of the year allows more or less sunlight penetration, resulting in deliberate modification of the microclimate composition and thermal conditions provided to animals. In this sense, the aims of this study were to evaluate microclimatic variables and thermal comfort indices for east-west and north-south oriented silvopastoral systems, compared to unshaded systems during summer and winter. The study was conducted at the Modelo II Farm (21° 08’ S 53° 17’ W) at an altitude of 354 m. A randomized block design in scheme of split-split plots with five repetitions was adopted. Two planting directions and a control treatment (unshaded) were evaluated in the plots. Collection times were evaluated in sub-plots, and the distance from eucalyptus trees was evaluated in sub-sub-plots. Changes in the east-west and north-south planting directions did not promote changes in climate variables, nor did they change the thermal comfort indices during summer. There were differences, however, in temperature and relative humidity of the air, black globe temperature, and radiant heat load during winter. Silvopastoral systems provide improvements in the environment and, concomitantly, to the thermal comfort of animals, when compared to unshaded systems. However, thermal stress situations occur despite the presence of trees, depending on the time of the day and the distance from the rows of eucalyptus trees.